Pengembangan Modul Berbasis Problem Based Learning pada Materi Statistika SMP Kelas VIII - Nofri Aldo; Rena Revita; Erdawati Nurdin (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This research aims to develop a valid, practical, and effective eighth-grade Statistical module based on Problem-Based Learning. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) model was used to develop the module in this research. The research findings showed that the developed module was valid with a validity percentage of 85.29% based on the validity test. Based on the practicality test of a small group with eight respondents, the developed module was stated very practical with a practicality percentage of 88.97%. These showed that the developed module completed valid and practical criteria. The practicality test of limited group and module effectiveness test could not be carried out because the learning situation was not effecting during the COVID-19 pandemic.